2020
DOI: 10.1093/gigascience/giaa137
|View full text |Cite
|
Sign up to set email alerts
|

Long-read assembly of the Brassica napus reference genome Darmor-bzh

Abstract: Background The combination of long reads and long-range information to produce genome assemblies is now accepted as a common standard. This strategy not only allows access to the gene catalogue of a given species but also reveals the architecture and organization of chromosomes, including complex regions such as telomeres and centromeres. The Brassica genus is not exempt, and many assemblies based on long reads are now available. The reference genome for Brassica napus, Darmor-bzh, which was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 53 publications
4
108
0
Order By: Relevance
“…The Darmor-bzh 4.1 reference assembly was constructed prior to the advance of long-read sequencing technologies mainly based on Illumina short-read sequencing and is thus highly fragmented (Lee et al, 2020). We have to note that between the submission and publication of this article, an upgraded, Oxford Nanoporebased version of Darmor-bzh genome (v10) was published, in which the region in question is assembled in agreement with the results of our study and other long-read assemblies (Rousseau-Gueutin et al, 2020). Moreover, it has been shown that in B. napus more than 50% of known RGA copies do not occur in a single reference genotype assembly but require analysis of pangenome assemblies for detection (Dolatabadian et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…The Darmor-bzh 4.1 reference assembly was constructed prior to the advance of long-read sequencing technologies mainly based on Illumina short-read sequencing and is thus highly fragmented (Lee et al, 2020). We have to note that between the submission and publication of this article, an upgraded, Oxford Nanoporebased version of Darmor-bzh genome (v10) was published, in which the region in question is assembled in agreement with the results of our study and other long-read assemblies (Rousseau-Gueutin et al, 2020). Moreover, it has been shown that in B. napus more than 50% of known RGA copies do not occur in a single reference genotype assembly but require analysis of pangenome assemblies for detection (Dolatabadian et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…The context sequences of each SNP marker were physically localized on the reference genome B. rapa Chiifu v1.5 [45] and B. napus cv. Darmor-bzh v10 [46] using BLASTn (ver. 2.9.0, min.…”
Section: Dna Extraction and Snp Genotypingmentioning
confidence: 99%
“…Darmor A01 chromosome was selected for its pericentromeric localization. The context sequences of the SNP markers (derived from Brassica 60 K Illumina infinium array) flanking this QTL were retrieved and physically localized on the B. napus reference genome Darmor-bzh v10 [46] using BLASTn [47].…”
Section: Localization Of a Qtl Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene prediction was performed using several proteomes: 8 from other genotypes of B. napus [51] (Westar, Zs11, QuintaA, Zheyou73, N02127, GanganF73, Tapidor3, and Shen-gli3), Arabidopsis thaliana (UP000006548) and the 2021 annotation of Darmor-bzh [30]. Regions of low complexity in genomic sequences were masked with the DustMasker algorithms [52] (version 1.0.0 from the blast 2.10.0 package).…”
Section: Gene Predictionmentioning
confidence: 99%